Should American Antitrust Laws Protect Only American Consumers? - Phan, Thanh (American Journal of Trade and Policy, 2017)
The United States adopted its first antitrust statute in 1890. Despite their long history of development, American antitrust laws do not specify any objectives. The primary objective of the American antitrust laws centers a long-standing debate among many scholars. This paper firstly argues that the American antitrust laws were designed to promote consumer welfare. However, exemptions for export cartels confine the concept of “consumers” protected by the Sherman Act to those in the U.S territory. This paper secondly proposes that exemptions for export cartels should be abolished for two reasons. First, the exemptions make American antitrust policy inconsistent because they do not reflect the objective that promotes consumer welfare. Second, from an international perspective, exemptions for export cartels are inconsistent with the efforts of the American Government to apply the Sherman Act extraterritorially—a measure that aims to protect consumers from international cartels.